Motivasi Masyarakat dalam Pemanfaatan Internet untuk Pengelolaan Sampah di Kecamatan Banyumanik Kota Semarang - Vionna Vionna; Maryono Maryono (School of Postgraduate Studies, Diponegoro Univer, 2019)
Motivation in waste management is one of the driving factors for realizing Smart Waste Management (SWM). The motivation is aimed at being able to change people's behavior in waste management from gathering to waste to reducing and handling the community that can be done through technology assistance in its management system known as the Internet of Things (IoT). Data were collected from 200 respondents who had been served garbage facilities and had used the internet in Banyumanik District using a 1-7 Likert scale. Using Structural Equation Modeling (SEM), this study examines the factors that influence people's motivation in using the internet for waste management. Based on the socio-demographic, economic and solid waste systems in Banyumanik Subdistrict, the researchers found that knowledge of the internet and recycling factors were the most important factors that influenced people's motivation with a correlation coefficient of 1.02. Another influential factor is the condition of the waste facility itself with a correlation coefficient of 0.74. Thus, this study recommends that the government to promote IoT for waste management such as the existence of educational applications about solid waste before continuing on improving the quality of waste facilities equipped with smart components such as sensors, GPS, and others.